Infodemiology of Rabies in Indonesia and Neighboring Countries: Insights from Google Trends (2020–2024) - Agil Wahyu Wicaksono; Fatiha Kamilah; Dinda Iryawati (Universitas Ahmad Dahlan, 2026)
Background: As Asian countries struggle to meet the global